The Effectiveness of Problem-Based Learning on Mathematical Connections in Terms of the Student's Learning Style - Herlambang, Satriya; Kartono, Kartono; Isnarto, Isnarto (Educational Management, 2021)
This study aimed at determining the effectiveness of problem-based learning (PBL) on the ability of mathematical connections in terms of learning styles. The research type was Sequential Explanatory type of the Mixed Method. The population was class IV consisting of two classes, class A with 28 students as the experimental class and class B with 28 students as the class control. These classes were also the sample. The data collection techniques were tests, questionnaires, and interviews. The data analysis methods were the average completeness test, classical completeness test, and average difference test. The study showed: The ethnomathematical teaching of the PBL model was efficacious on students' mathematical connections abilities. It was proven on (1) the ability of mathematical connections using PBL model including ethnomathematical reaching the KKM individually; (2) the classical completeness reached 75%; (3) the average of mathematical connections ability of students in the experimental class was more than the control class. Analysis of students' mathematical connections abilities based on learning styles showed every student with visual, auditory, or kinesthetics learning styles was able to complete the test according to the indicators.